Perceptions of traditional health practitioners and radiation oncologists regarding referral of cancer patients in a cooperative practice in KwaZulu-Natal province, South Africa - Pauline Busisiwe Nkosi; Maureen Nokuthula Sibiya (Elsevier, 2018)
The referral system is an important component of the health care system, exclusively in a cooperative practice. The objective of this study was to explore the perceptions of traditional health practitioners and radiation oncologists regarding referral of cancer patients. The study was conducted in KwaZulu-Natal, South Africa and employed a qualitative explorative descriptive design. Snowball and purposive sampling techniques were utilised to recruit participants from traditional health practitioners and radiation oncologists, respectively. Interviews were conducted in isiZulu for the former and English in the latter. The data was saturated with 28 traditional health practitioners and four radiation oncologists. All the interviews were audio-taped and transcribed verbatim. Interview data from traditional health practitioners was first translated back to English before data analysis.The traditional health practitioners referred patients to the hospital and not the radiations oncologists and there was no referral from the radiation oncologists. Both parties value cooperative practice but were still wrestling with traditional health practitioners' own locally developed practices of traditional medicine use. Traditional health practitioners were willing to provide evidence of their practices in order to demonstrate their role and practices in cancer treatment. They suggested other strategies to ensure a working relationship and patients' referral. Keywords: Patients' referral, Traditional health practitioners, Radiation oncologists, Cancer patients, Cooperative practice, Qualitative study